2020
DOI: 10.1093/neuonc/noaa222.336
|View full text |Cite
|
Sign up to set email alerts
|

HGG-57. Whole-Genome Sequencing, Methylation Analysis, and Single-Cell Rna-Seq Define Unique Characteristics of Pediatric Treatment-Induced High-Grade Glioma and Suggest Oncogenic Mechanisms

Abstract: BACKGROUND Pediatric treatment-induced high-grade glioma (TIHGG) is among the most severe late effects observed in childhood cancer survivors and is uniformly fatal. We previously showed that TIHGG are divergent from de novo pediatric high-grade glioma (pHGG) and cluster into two gene expression subgroups, one stemlike and the other inflammatory. Here we systematically compared TIHGG molecular profiles to pHGG and evaluated expression and single cell sequencing profiles in order to identify o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The correlation of recurrent RIG genetic alterations with those observed in the methylation subclass pedGBM_RTK1, and the positive association of the TK-RIG915 PDX with this methylation class, raises the question of whether other RIGs would cluster similarly using DNA methylation-based techniques. Furthermore, preliminary data by Lucas et al 90 corroborate our assessment, where they report that RIG DNA methylation profiles are similar to pedGBM_RTK1 methylation subgroup tumors. Additional research using a larger number of samples is essential to determine whether RIGs truly are genetically similar to pediatric GBM or if they represent a unique tumor subclass.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The correlation of recurrent RIG genetic alterations with those observed in the methylation subclass pedGBM_RTK1, and the positive association of the TK-RIG915 PDX with this methylation class, raises the question of whether other RIGs would cluster similarly using DNA methylation-based techniques. Furthermore, preliminary data by Lucas et al 90 corroborate our assessment, where they report that RIG DNA methylation profiles are similar to pedGBM_RTK1 methylation subgroup tumors. Additional research using a larger number of samples is essential to determine whether RIGs truly are genetically similar to pediatric GBM or if they represent a unique tumor subclass.…”
Section: Discussionsupporting
confidence: 87%
“…Preliminary data from others support this correlation, with 26 out of 36 gliomas that developed after therapy clustering with the pedGBM_RTK1 subgroup by methylation array. 90 In summary, despite most RIGs being diagnosed in adulthood, 16 our comparisons of cranial RIGs with multiple other types of glioma revealed that these tumors most closely resemble the pedGBM_RTK1 molecular subgroup of pediatric gliomas (depicted in Figure 5 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations